The HIV‐1 gp41 ectodomain is cleaved by matriptase to produce a chemotactic peptide that acts through FPR2. Issue 3 (July 2014) - Wood, Matthew P.; Cole, Amy L.; Eade, Colleen R.; Chen, Li‐Mei; Chai, Karl X.; Cole, Alexander M.
Summary Several aspects of HIV‐1 virulence and pathogenesis are mediated by the envelope protein gp41. Additionally, peptides derived from the gp41 ectodomain have been shown to induce chemotaxis in monocytes and neutrophils. Whereas this chemotactic activity has been reported, it is not known how these peptides could be produced under biological conditions. The heptad repeat 1 (HR1) region of gp41 is exposed to the extracellular environment and could therefore be susceptible to proteolytic processing into smaller peptides. Matriptase is a serine protease expressed at the surface of most epithelia, including the prostate and mucosal surfaces. Here, we present evidence that matriptase efficiently cleaves the HR1 portion of gp41 into a 22‐residue chemotactic peptide MAT‐1, the sequence of which is highly conserved across HIV‐1 clades. We found that MAT‐1 induced migration of primary neutrophils and monocytes, the latter of which act as a cellular reservoir of HIV during early stage infection. We then used formyl peptide receptor 1 (FPR1) and FPR2 inhibitors, along with HEK 293 cells, to demonstrate that MAT‐1 can induce chemotaxis specifically using FPR2, a receptor found on the surface of monocytes, macrophages and neutrophils. These findings are the first to identify a proteolytic cleavage product of gp41 with chemotactic activity and highlight a potential role for matriptase in HIV‐1 transmission and infection at epithelial surfaces and within tissue reservoirs of HIV‐1.